APPLICATION OF THE PICTURE AND PICTURE METHOD TO ENHANCE STUDENTS’ CHRONOLOGICAL THINKING SKILLS IN HISTORY LEARNING AT SMA NEGERI 1 KABILA - Kiayi, Zuhriyati; Mohamad, Sutrisno; Arrazaq, Naufal Raffi (CV. Fahr Publishing, 2025)
This study was conducted with the aim of measuring the extent of students’ chronological thinking skills in class X-5 after the implementation of the Picture and Picture method. The research employed a Classroom Action Research (CAR) approach carried out in two cycles. The subjects consisted of 36 students, representing the entire X-5 class. Data collection techniques included observation, interviews, and documentation, using instruments such as observation sheets, interview guidelines, and learning outcome tests. The findings revealed that the application of the Picture and Picture method improved students’ chronological thinking skills. This was evident from the increase in the average learning outcomes, which initially fell into the “fair” category and later improved to the “good” category, with percentages rising from 57.6% to 87.2%. Furthermore, improvements were also observed in students’ performance aspects, increasing from 32.8% to 51.2%. Data were analyzed using descriptive quantitative and qualitative methods, leading to the conclusion that the Picture and Picture method is effective in enhancing students’ chronological thinking skills.